Novel Linear and Hyperbranched Polythiophene Derivatives Containing Diketopyrrolopyrroles as Linking Groups. Issue 1771 (19th May 2015) - Yang, Sheng-Hsiung; Hsieh, Chia-Hao
ABSTRACT: The goal of this research is to synthesize novel linear and hyperbranched polythiophene derivatives containing diketopyrrolopyrrole (DPP) as linking groups, and to investigate thermal, optical, electrochemical, and photovoltaic properties of those derivatives. Polymers with high regioregularity were synthesized via the Universal Grignard metathesis polymerization. Those linear or hyperbranched polythiophenes containing DPP bridging moieties showed higher molecular weights and better thermal stability compared with normal P3HT. The UV-vis absorption spectra of the DPP-containing polymers are similar to that of P3HT in film state, while they show distinct attenuation in fluorescent emission. Finally, all polymers were blended with PC61 BM and used as active layers for fabrication of inverted solar devices. The devices based on those DPP-containing polythiophenes revealed the open-circuit voltage ( V OC ) of 0.55–0.58 V, the short-circuit current ( J SC ) of 8.62–16.21 mA/cm 2, the fill factor ( FF ) of 36–41%, and the power conversion efficiency ( PCE ) of 1.73–3.74%.